Luminal Plasma Treatment for Small Diameter Polyvinyl Alcohol Tubular Scaffolds - Pohan, Grace; Chevallier, Pascale; Anderson, Deirdre E. J.; Tse, John W.; Yao, Yuan; Hagen, Matthew W.; Mantovani, Diego; Hinds, Monica T.; Yim, Evelyn K. F. (Frontiers in Bioengineering and Biotechnology, 2019)
Plasma-based surface modification is recognized as an effective way to activate biomaterial surfaces, and modulate their interactions with cells, extracellular matrix proteins, and other materials. However, treatment of a luminal surface of a tubular scaffold remains non-trivial to perform in small diameter tubes. Polyvinyl alcohol (PVA) hydrogel, which has been widely used for medical applications, lacks functional groups to mediate cell attachment. This poses an issue for vascular applications, as endothelialization in a vascular graft lumen is crucial to maintain long term graft patency. In this study, a Radio Frequency Glow Discharges (RFGD) treatment in the presence of NH3 was used to modify the luminal surface of 3-mm diameter dehydrated PVA vascular grafts. The grafted nitrogen containing functional groups demonstrated stability, and in vitro endothelialization was successfully maintained for at least 30 days. The plasma-modified PVA displayed a higher percentage of carbonyl groups over the untreated PVA control. Plasma treatment on PVA patterned with microtopographies was also studied, with only the concave microlenses topography demonstrating a significant increase in platelet adhesion. Thus, the study has shown the possibility of modifying a small diameter hydrogel tubular scaffold with the RFGD plasma treatment technique and demonstrated stability in ambient storage conditions for up to 30 days.